Patient-tailored approach for enhanced recovery after surgery - Seyfried, Steffen; Herrle, Florian; Téoule, Patrick; Betzler, Alexander; Reißfelder, Christoph (Visceral medicine, 2022)
Background: Enhanced recovery after surgery (ERAS®) is increasingly finding its way into clinical practice. ERAS® protocols have not been universally adopted, and they have often been criticized for being difficult to implement. So, the question for more tailor-made approaches arises. Methods: We conducted a literature search on March 16, 2022, using the following search string, which was modified to fit the input of each of the queried databases: (“ERAS®” or “enhanced recovery after surgery” or “fast recovery” or “fast track”) and (“tailored” or “individual”). Results: Despite the massive increase in general hits on the subject, stratification according to phenotypic characteristics such as age or a classification according to disease patterns in the sense of specific guidelines is still fundamentally apparent. Evidence suggests that generic protocols can be followed by almost all patients. Prehabilitation, in particular, can be used as an adaptive tool. Conclusion: ERAS® works only in the totality of its tools and can be followed by almost all patients. Prehabilitation is more adaptive and can also increase adherence to ERAS® protocols. A tailored program outside of disease-specific pathways does not seem to be useful.